A Visualized Analysis of Cultural Teaching in International Chinese Language Education: A Bibliometric Study Based on CiteSpace: 国际汉语教育中文化教学研究的可视化分析——基于CiteSpace的计量研究 - Sukma Tajuddin; Sukma; Asmuliyati Nahnu (Published by Confucius Institute UNS, 2025)
Driven by the “Chinese culture going global” strategy and the Belt and Road Initiative, cultural instruction has increasingly become a crucial component of international Chinese language education. Based on 487 CSSCI and core journal articles from the CNKI database published between 2016 and 2025, this study employs CiteSpace 6.3.R1 to analyze the research hotspots and evolutionary paths of this field from the perspectives of keyword co-occurrence, clustering, burst detection, and author–institution collaboration. The findings reveal that the research focus in cultural teaching has shifted from “traditional cultural dissemination” to “intercultural integration,” with key hotspots centering on tea culture, Confucius Institutes, and professional degree programs. Collaborative networks show a growing trend toward clustering, and several keywords exhibit strong burst intensity and long duration, indicating sustained academic attention in this field. This study helps clarify the knowledge structure of cultural instruction and provides theoretical support and practical guidance for future topic development, paradigm construction, and pedagogical innovation.